"Study of the Biological Treatment of Industrial Waste Water by the Activated Sludge Unit" - MK Sharifi-Yazdi; C Azimi; MB Khalili (Tehran University of Medical Sciences, 2001)
The activated sludge process simply involves bringing together wastewater and a mixed culture of microorganisms under aerobic conditions. The system usually includes a secondary treatment given to the settled sewage, and requires an environment in which active microorganisms are maintained in intimate contact with wastewater in the presence of sufficient oxygen. In this study, the treatment of industrial effluents, by using laboratory activated sludge unit was investigated. The reduction of the pollution laws was determined, using the biochemical oxygen demand (BOD) and the chemical oxygen demand (COD) methods. The results indicated that the pollution laws was reduced by up to 98% in the activated sludge unit.